Kh̄ư phūying kh̄ư kammak̜ōn : kātūn phưa chīwit thī dīkwā samrap kh̜ōngān ying ʻĒsia : khūmư kh̜on thām kitʻchakam dān r̄ængngān - Cheung, Choi Wan (Fāi R̄ængngān ying Nai Phāk ʻƯtsāhakam Kānphalit Mūnnithi Ph̄ưan Ying, 1998)
Cartoon displaying work role of women.